La relazione pedagogica nella Grecia classica tra violenza e cura - Valeria Andò (Firenze University Press, 2009)
In Ancient Greek education has been idealized (we can think to paideia and the socratic thougth) but that educational sistem provided for violence methods. The authoritative lingauge and the severity of discipline are jointed to a process of care. This moment is very important to carry out a significant style of life.